2016
DOI: 10.1002/psp4.12081
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Design of Anti‐Transferrin Receptor Bispecific Antibodies for Optimal Delivery into the Human Brain

Abstract: Anti‐transferrin receptor (TfR)‐based bispecific antibodies have shown promise for boosting antibody uptake in the brain. Nevertheless, there are limited data on the molecular properties, including affinity required for successful development of TfR‐based therapeutics. A complex nonmonotonic relationship exists between affinity of the anti‐TfR arm and brain uptake at therapeutically relevant doses. However, the quantitative nature of this relationship and its translatability to humans is heretofore unexplored.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Whereas this data could not be fully explained in the absence of the measurements of these antibodies in the interstitial fluid (ISF), they underscore the importance of incorporating central (brain) target abundance in developing pharmacokinetic> pharmacodynamic (PK>PD) models for BBB>crossing bi>specific molecules. In a prior study30 we have shown that systemically administered high>affinity antibody against mGluR1, an abundant central target, fused to an alternative BBB carrier, displays higher brain levels in combination with lower CSF exposure compared to the BBB>fused antibody that has no central target, suggesting that the high fraction of 'bound' antibody reduces 'free' antibody available for the exchange with CSF 43. In the case of anti>TfR antibodies, the target is highly expressed in both peripheral and central compartments, and their affinity could significantly affect not only systemic pharmacokinetics and BBB delivery, but also their central disposition (unbound fraction) and pharmacology.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas this data could not be fully explained in the absence of the measurements of these antibodies in the interstitial fluid (ISF), they underscore the importance of incorporating central (brain) target abundance in developing pharmacokinetic> pharmacodynamic (PK>PD) models for BBB>crossing bi>specific molecules. In a prior study30 we have shown that systemically administered high>affinity antibody against mGluR1, an abundant central target, fused to an alternative BBB carrier, displays higher brain levels in combination with lower CSF exposure compared to the BBB>fused antibody that has no central target, suggesting that the high fraction of 'bound' antibody reduces 'free' antibody available for the exchange with CSF 43. In the case of anti>TfR antibodies, the target is highly expressed in both peripheral and central compartments, and their affinity could significantly affect not only systemic pharmacokinetics and BBB delivery, but also their central disposition (unbound fraction) and pharmacology.…”
mentioning
confidence: 99%
“…Therefore, this translational complexity of the target (TfR) including inter>species variability and pharmacokinetic and toxicity liabilities will remain serious obstacles in the development of clinically viable brain>targeting bi>specific molecules using TfR antibodies as BBB>crossing carriers. A further interesting observation from PK>PD modeling studies with TfR>BACE1 bi>specific antibodies42,43 is that the 'benefit' of TfR variants in improving antibody brain penetration is expected only when the antibody recognizes intermediately or highly abundant target in periphery, but will be negligible for antibodies with low abundant peripheral…”
mentioning
confidence: 99%
“…Poor, individually variable antibody penetration into the CNS may well have played an important role for these failures. Strategies to enhance delivery of systemically administered exogenous antibodies to the CNS such as transient disruption of the BBB with focused ultrasound [18,19] or shuttling constructs across the BBB [20][21][22] are being developed but have not stood the tests for clinical routine yet. Our study reveals that antibody delivery to the CNS remains challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Taking advantage of this Tf/TfR system, attempts to transport therapeutics across the BBB have been made (e.g., bispecific antibodies). 25,26 Although the utilization of TfR to cross the BBB has been investigated in rodents for decades, success in translating these findings to humans remains elusive. 27 The issue causing some such therapeutics to fail is connected to the affinity of the antibodies being used, the pH dependence of their dissociation from the TfR, and how differences between antibodies influence the fate of both the antibody conjugate and the TfR to which it binds.…”
Section: Discussionmentioning
confidence: 99%